Drivers of and barriers to the SME internationalisation process in a small open economy - Brochado, A.; Lobo, C.; Pacheco, L.; Maldonado, I. (Economics Bulletin, 2020)
Small and medium-sized enterprises (SMEs) have actively increased their participation in international markets. This research's primary objective was to identify, based on 11 case studies, the main barriers to and drivers of the SME internationalisation process in a small open economy. Content analysis of in-depth interviews used Leximancer software to identify 7 themes that describe both internal and external barriers and 12 themes that characterise drivers, which were classified into five groups: SME human capital, technology, institutional support, networks and other drivers.